Chronic disseminated intravascular coagulation induced by left atrial thrombus in a patient with giant "normal" heart: A case report. Issue 51 (December 2016) - Shao, Qianqian; Tian, Ran; Zhang, Xu; Gao, Xin; Lai, Jinzhi; Tian, Zhuang; Yan, Xiaowei; Zhang, Shuyang
Abstract: Introduction: We herein describe a patient with chronic disseminated intravascular coagulation (DIC) induced by a giant thrombus in the left atrium. A 63-year-old woman was admitted to our hospital for evaluation of extensive mucocutaneous hemorrhage, especially at the sites of venipuncture, on May 21, 2015. Considering her long history of rheumatic heart disease and atrial fibrillation and her mitral valve replacement performed several years previously, we strongly suspected that the bleeding was closely related to postoperative over-anticoagulation of warfarin. After careful investigation, we found that her coagulopathy was induced by the chronic DIC, which was in turn secondary to a left atrial giant thrombus. This is a rarely reported cause of chronic DIC. Cardiac computed tomography and echocardiography showed apparent biatrial enlargement; the morphology and function of the ventricles were unaffected. After anticoagulant therapy, the bleeding tendency and coagulation index were significantly improved. Conclusion: A left atrial thrombus should be considered as a differential diagnosis of chronic DIC, especially in patients with predisposing heart conditions. Because treatment of the underlying cause is paramount in the management of chronic DIC, this case is of great clinical value.